MOTIVASI WISATAWAN MANCANEGARA LANJUT USIA BERWISATA DI BALI: STUDI KOMPARASI WISATAWAN MANCANEGARA ASIA DAN NON-ASIA - Faustina Lianto (Jurnal Hospitality dan Manajemen Jasa, 2017)
Tujuan penelitian ini adalah untuk mengidentifikasi faktor-faktor pendorong dan penarik motivasi wisatawan mancanegara lanjut usia Asia dan non-Asia dalam memilih Bali sebagai destinasi wisata, serta mengkaji apakah terdapat perbedaan faktor pendorong dan penarik antara 2 kelompok kebangsaan ini. Jenis penelitian yang dilakukan adalah kuantitatif deskriptif dengan metode analisa faktor, yang selanjutnya dilakukan analisis komparatif. Hasil analisis faktor membentuk 6 faktor pendorong, yaitu 1) explore and increase knowledge about the local culture, 2) quality time and visiting nostalgic places with close accompanies, 3) relaxation and having fun, 4) spending time with family members, 5) rejuvenation and health, 6) sharing destination experience. Selain itu terungkap 4 faktor penarik baru, yaitu 1) hospitality services and tourism attractions, 2) local culture, 3) natural scenery and climate, 4) quite rest area. Lebih lanjut, terdapat 2 faktor dengan perbedaan yang signifikan dan 4 faktor dengan perbedaan yang tidak signifikan pada analisis komparasi faktor pendorong, sedangkan untuk faktor penarik ditemukan tidak terdapat perbedaan yang signifikan faktor pendorong antara wisatawan mancanegara lanjut usia Asia dan non-Asia. This research focused on senior foreign travelers aiming to identify the push and pull factors of Asian and non-Asian travelers in choosing Bali as their travel destination. It also aimed to review whether there were differences between push and pull factors. Factor analysis was applied to identify the push and pull factors, while independent sample t-test was chosen to determine those significant differences between those 2 nationality groups. The results showed that there were 6 push factors, they were 1) explore and increase knowledge about the local culture, 2) quality time and visiting nostalgic places with close accompanies,3) relaxation and having fun, 4) spending time with family members, 5) rejuvenation and health, 6) sharing destination experience. And another 4 pull factors, they were 1) hospitality services and tourism attractions, 2) local culture, 3) natural scenery and climate, 4) quite rest area. Those are motivating respondents to choose Bali as their travel destination. The comparative analysis of the push factors also showed that there were significant differences of motivation; whereas for the pull motivational factors, there were no significant differences for the Asian and non-Asian senior tourists.